Linguistics and foreign language teaching methodology - Piesarskas, B. (Psichologija, 1963)
There are two parts to this article.The first part provides a brief critical overview of Soviet linguists and methodologists opinions on the subject.The second part addresses the most important linguist statements relevant in terms of foreign language teaching methodology theory. These are they:1)      Language is the main means of communication between people2)      Language and speech are closely interrelated3)      Thinking and language are united
Keywords: Linguistics and foreign language teaching methodology